Corporate Financial Performance and the Intervening Role of Energy Operating Costs: The Case of Jordanian Electricity Sector - Aladwan, Mohammad; Alsinglawi, Omar; Alhawatmeh, Omar M.; Almaharmeh, Mohammad (International Journal of Energy Economics and Policy, 2023)
This paper analyzes the impact of financial performance reported data on market value. The study was conducted on electricity companies for the period 2011 to 2021. The study also empirically analysis the intervening role for oil and gas as operating costs on this relationship. The empirical analysis involved testing the direct effect for company size (TA), profitability (ROE), debt (DR), liquidity (CR) and oil and gas price (OG-P) as independent variables on market value measured by price to book value (P-BV) as dependent variable. Several statistical test were used in the study comprise correlation, simple and multiple regression through Ordinary Least Square (OLS) in order to verify the effect of independent and mediating variables on the dependent variable. The main findings based on correlation, simple and multiple regression can be summarized as follows: independent variables namely ROE, CR and the mediating variable OG-P were found statistically significant and justified the change in market value; other factors TA and DR failed to prove any effect on market value of companies. The oil and gas costs confirmed their impact on market value as single variables effect and joint variable effect.